Exercise and nutrition in mitochondrial disorders - Tarnopolsky, Mark (Henry Stewart Talks, 2018)
Methods used in diagnosing mitochondrial cytopathies, Common cellular metabolic pathways altered by mitochondrial dysfunction, Evaluation of nutritional intake in patients with mitochondrial disease, The use of exercise and nutrition for treatment of mitochondrial disorders, Clinical evaluation of the role of exercise and nutrition